Effect of Benson Relaxation Therapy on Postoperative Pain among Patients with Fractures - Muhammad Husein Haykal; Linda; Dewi Nurhanifah; Uni Afriyanti (Fakultas Kedokteran, Universitas Papua, 2026)
Postoperative pain is one of the most common clinical problems experienced by patients with fractures and may delay recovery. Benson Relaxation Therapy is a non-pharmacological intervention that may help reduce pain intensity. This study aimed to examine the effect of Benson Relaxation Therapy on postoperative pain among patients with fractures. A pre-experimental study with a one-group pretest–posttest design was conducted involving 34 patients with fractures recruited using accidental sampling. Pain intensity was assessed using a pain scale before and after the intervention and analyzed using the Wilcoxon Signed Rank Test. Before the intervention, most participants experienced moderate pain (91.2%), whereas after the intervention the majority reported mild pain (76.5%). The Wilcoxon Signed Rank Test demonstrated a significant difference in pain intensity before and after the intervention (p = 0.001). Benson Relaxation Therapy had a significant effect on reducing postoperative pain among patients with fractures.